Socioeconomic Factors Affecting Labor Unions in Pakistan: A case study of Public Sector Organizations - Bashir, Furrukh; Akhtar, Muhammad Aslam (iRASD Journal of Management, 2022)
The study focuses on socioeconomic factors motivating labor to become part of labor unions in Pakistan. Various socioeconomic variables were chosen and tested their impact on employees’ decision of joining union. The sample comprises of the respondents working in Pakistan international Airline, State bank and MEPCO. A total of 214 responses were collected through questionnaire via simple random sampling technique. In order to observe the effect of independent variables i.e. income, age, sex, education, marital status, household size and loan are examined on dependent variable i.e. peer family influence, job environment satisfaction, satisfaction with union and financial benefits associated with union. Employing regression tests, it was analyzed that family peer influence is negatively affected by education, household size, loan taken and by age. The results further indicate that job environment satisfaction is positively affected by age. The study also found that satisfaction with union is positively affected by education whereas it is negatively affected by marital status and household size. This research also concluded that financial benefits associated with union is positively affected by salary, education and age whereas it is negatively affected by marital status, household size and loan taken.